Partial amniotic carbon dioxide insufflation for fetal surgery. (28th October 2018) - Skinner, Sasha; DeKoninck, Philip; Crossley, Kelly; Amberg, Benjamin; Deprest, Jan; Hooper, Stuart; Hodges, Ryan
Abstract: Partial amniotic carbon dioxide insufflation (PACI) involves insufflating the amniotic sac with carbon dioxide (CO2 ) and, in some cases, draining some of the amniotic fluid. The creation of a gaseous intra‐amniotic compartment improves visualization, even in the presence of limited bleeding, and creates the work space required for complex fetoscopic procedures. Clinically, PACI is mostly used to perform fetoscopic myelomeningocele (MMC) repair, enabling a minimally invasive alternative to open fetal surgery. However, evidence of the fetal safety of PACI is limited. Previous animal experiments in sheep demonstrate that PACI induces fetal hypercapnia and acidosis with largely unknown short and longer term implications. In this review, we examine the literature for the physiological effects of intrauterine insufflation pressure, duration, humidity, and the role of maternal hyperventilation on fetal physiology and well‐being. Abstract : What is already known about this topic? PACI causes fetal hypercapnia and acidosis in sheep. Early case series of fetoscopic MMC repair using PACI reported high rates of preterm premature rupture of the membranes (PPROM) and preterm birth, however recent case series describe improved pregnancy outcomes. Limited clinical series using PACI do not show abnormal neurological development in operated fetuses. What does this study add? Comprehensive review of literature from animal and clinical studies relating to PACI Discuss possible mechanisms and effects of PACI insufflation pressure, duration, humidity, and maternal hyperventilation on fetal physiology and well‐being.